2020
DOI: 10.3389/fneur.2020.601286
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Pediatric Traumatic Brain Injury

Abstract: There has been a growing interest in the potential of stem cell transplantation as therapy for pediatric brain injuries. Studies in pre-clinical models of pediatric brain injury such as Traumatic Brain Injury (TBI) and neonatal hypoxia-ischemia (HI) have contributed to our understanding of the roles of endogenous stem cells in repair processes and functional recovery following brain injury, and the effects of exogenous stem cell transplantation on recovery from brain injury. Although only a handful of studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…Using this system, we established the role of NMII in neurite generation, as well as its upstream regulation by the RhoA/ROCK1 signaling pathway. These results may provide new perspectives in the development of stem cells therapies as NMII might be considered as a novel drug target for integrating transplanted cells in neurodegenerative disorders, such as Parkinson's and Alzheimer's diseases, as well as in traumatic brain and spinal cord injuries (Ford et al, 2020;Lengel et al, 2020;Liu et al, 2020;Parmar et al, 2020;Bagheri-Mohammadi, 2021;Hu et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Using this system, we established the role of NMII in neurite generation, as well as its upstream regulation by the RhoA/ROCK1 signaling pathway. These results may provide new perspectives in the development of stem cells therapies as NMII might be considered as a novel drug target for integrating transplanted cells in neurodegenerative disorders, such as Parkinson's and Alzheimer's diseases, as well as in traumatic brain and spinal cord injuries (Ford et al, 2020;Lengel et al, 2020;Liu et al, 2020;Parmar et al, 2020;Bagheri-Mohammadi, 2021;Hu et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…In the mid-2000s, clinical studies began on the effectiveness of CB use in patients with neurological pathology. Pilot and clinical trials involving pediatric patients with conditions such as hypoxic-ischemic encephalopathy, cerebral palsy, autism spectrum disorder and acquired hearing loss have confirmed the safety and efficacy of cryopreserved autologous and allogeneic CB [17][18][19][20][21][22]. A phase I clinical trial also confirmed the safety and appropriateness of allogeneic unrelated umbilical cord blood in adult patients with ischemic stroke [23].…”
Section: The Current State Of Cord Blood Banks and The Use Of Cord Blood Stem Cells In The Worldmentioning
confidence: 98%
“…Preclinical research has demonstrated the potential therapeutic usefulness of stem cell therapy. In preclinical research, neuroprotective and regenerative capabilities of stem cells have been proposed as the mechanism of action 24 . In recent years, research has discovered that a number of stem cells, including MSCs, NSCs, multipotent adult progenitor cells (MAPCs), and EPCs, can heal neurological damage following TBI 25 .…”
Section: Diseases Amenable To Cell‐based Therapiesmentioning
confidence: 99%
“…In preclinical research, neuroprotective and regenerative capabilities of stem cells have been proposed as the mechanism of action. 24 In recent years, research has discovered that a number of stem cells, including MSCs, NSCs, multipotent adult progenitor cells (MAPCs), and EPCs, can heal neurological damage following TBI. 25 STEMTRA, a recently completed phase 2 clinical trial (NCT02416492) that observed the potential effects of intracranial administration of bone marrow‐derived cells on patients with chronic motor deficit from TBI, discovered that significantly more patients receiving cell treatment showed enhanced motor status at 6 months in comparison to the patients receiving a control sham.…”
Section: Diseases Amenable To Cell‐based Therapiesmentioning
confidence: 99%